Being a Muslim Minority in Samosir: Resilience, Identity, and Coexistence under Christian Majority Dominance - Muhammad Roni (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2025)
This article explores the lived experiences of the Muslim minority in practicing their religious teachings within the predominantly Christian region of Samosir. It specifically investigates the resilience of the Muslim minority and how the Christian majority’s dominance influences the shaping of Muslim minority identity in Samosir. The data were collected through direct observation and in-depth interviews. This study employs Norman Garmezy’s (1995) theory of resilience and Pratto’s (1994) concept of dominance. Utilizing a field research design with a descriptive-analytical method and an ethnographic approach, this paper reveals how the contestation of power between the Christian majority and Muslim minority in Samosir has prompted Muslims to live out their faith in adaptive ways. The findings demonstrate that the Muslim minority in Samosir manages to withstand pressures from the majority due to three primary factors. First is voluntary acceptance; this willingness allows the Muslim minority to navigate daily life despite certain constraints. Second is the kinship factor, as Samosir, being part of the Toba region predominantly inhabited by the Batak people, upholds the cultural philosophy of Dalihan Na Tolu, which fosters social cohesion beyond religious lines. Third is the longevity of settlement; the Muslim minority has lived in Samosir for generations, which has strengthened their capacity to adapt and maintain harmonious relations. While various factors contribute to the resilience of Muslims under majority pressures, these three aspects emerge as the most significant. This study thus contributes to broader discussions on minority resilience, identity negotiation, and intergroup dynamics in plural societies, offering nuanced insights into how local cultural values and long-standing coexistence shape the durability of social harmony.